The role of activation functions 1 and 2 of estrogen receptor‐α for the effects of estradiol and selective estrogen receptor modulators in male mice. (17th April 2013) - Börjesson, Anna E; Farman, Helen H; Engdahl, Cecilia; Koskela, Antti; Sjögren, Klara; Kindblom, Jenny M; Stubelius, Alexandra; Islander, Ulrika; Carlsten, Hans; Antal, Maria Cristina; Krust, Andrée; Chambon, Pierre; et al.
Abstract Estradiol (E2) is important for male skeletal health and the effect of E2 is mediated via estrogen receptor (ER)‐α. This was demonstrated by the findings that men with an inactivating mutation in aromatase or a nonfunctional ERα had osteopenia and continued longitudinal growth after sexual maturation. The aim of the present study was to evaluate the role of different domains of ERα for the effects of E2 and selective estrogen receptor modulators (SERMs) on bone mass in males. Three mouse models lacking either ERαAF‐1 (ERαAF‐10), ERαAF‐2 (ERαAF‐20), or the total ERα (ERα−/−) were orchidectomized (orx) and treated with E2 or placebo. E2 treatment increased the trabecular and cortical bone mass and bone strength, whereas it reduced the thymus weight and bone marrow cellularity in orx wild type (WT) mice. These parameters did not respond to E2 treatment in orx ERα−/− or ERαAF‐20 mirx ERαAF‐10 mice were tissue‐dependent, with a clear response in cortical bone parameters and bone marrow cellularity, but no response in trabecular bone. To determine the role of ERαAF‐1 for the effects of SERMs, we treated orx WT and ERαAF‐10 mice with raloxifene (Ral), lasofoxifene (Las), bazedoxifene (Bza), or vehicle. These SERMs increased total body areal bone mineral density (BMD) and trabecular volumetric BMD to a similar extent in orx WT mice. Furthermore, only Las increased cortical thickness significantly and only Bza increased bone strength significantly. However, all SERMs showed a tendency toward increased cortical bone parameters. Importantly, all SERM effects were absent in the orx ERαAF‐10 mice. In conclusion, ERαAF‐2 is required for the estrogenic effects on all evaluated parameters, whereas the role of ERαAF‐1 is tissue‐specific. All evaluated effects of Ral, Las and Bza are dependent on a functional ERαAF‐1. Our findings might contribute to the development of bone‐specific SERMs in males. © 2013 American Society for Bone and Mineral Research.